2006
DOI: 10.1103/physrevb.74.104425
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the magnetic properties ofY2Ru2O7byRu

Abstract: Magnetic properties of the Mott insulator with the pyrochlore structure Y 2 Ru 2 O 7 were investigated using 99 Ru Mössbauer spectroscopy. Bulk magnetization measurements confirmed appearance of the spin-glass-like antiferromagnetic order with very large differences between zero-field-cooled and field-cooled magnetizations below the Néel temperature T N =76͑2͒ K. The Mössbauer spectra were obtained above and below T N . Analysis of the spectrum recorded at 4.2 K suggested a noncollinear local ordering of ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 26 publications
(32 reference statements)
2
25
0
Order By: Relevance
“…While magnetic properties of Nd 2 Ru 2 O 7 have been reported previously [7], we show here that the presence of ferromagnetic impurity phases compromised the earlier analysis. There has also been some confusion in the literature about the nature of the ordering of the Ru 4d spins in Nd 2 Ru 2 O 7 ; several reports have suggested that the ordering is glassy [8,9,10,11,12]. We find compelling evidence that Nd 2 Ru 2 O 7 is not a spin-glass, and propose a reason for the observed history-dependence of the ZFC-FC magnetic susceptibility and weak ferromagnetism below the ordering temperature.…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…While magnetic properties of Nd 2 Ru 2 O 7 have been reported previously [7], we show here that the presence of ferromagnetic impurity phases compromised the earlier analysis. There has also been some confusion in the literature about the nature of the ordering of the Ru 4d spins in Nd 2 Ru 2 O 7 ; several reports have suggested that the ordering is glassy [8,9,10,11,12]. We find compelling evidence that Nd 2 Ru 2 O 7 is not a spin-glass, and propose a reason for the observed history-dependence of the ZFC-FC magnetic susceptibility and weak ferromagnetism below the ordering temperature.…”
Section: Introductionmentioning
confidence: 53%
“…In particular, several reports have mentioned that the glassy nature of the ordering of Ru 4d spins is evident in bulk magnetic susceptibility measurements [8,9,10,11,12]. However, neutron diffraction experiments below the ordering temperature show that Ru spins order with a long correlation length [9,10].…”
Section: Magnetic and Electrical Transport Behaviourmentioning
confidence: 99%
“…3 The decrease of SOC with Ru substitution will presumably drive the system toward more collinear type AFM spin structure, yet the Mossbauer spectroscopy experiments have shown another end compound i.e., Y 2 Ru 2 O 7 is still a non-collinear type AFM system. 25 Moreover, recent calculations have shown that with increasing U the magnetic state in Y 2 Ir 2 O 7 moves from non-collinear AIAO state to AFM spin structure. 13,14 Therefore, the decreasing moment with x in present study (see Figs.…”
mentioning
confidence: 99%
“…8,9 Due to the usual nonmagnetic nature of the Eu 3+ ions, one would expect an intrinsic behaviour similar to that observed in the Y and Lu pyrochlores where no magnetic transitions occur at low temperatures. 10 This anomalous second magnetic transition has been systematically reported in the literature. [7][8] However, due to difficulties in performing neutron scattering experiments on Eu-based compounds, the precise nature of the observed ordering remains unknown.…”
Section: Introductionmentioning
confidence: 92%